THE EFFECTS OF VESICULAR ARBUSCULAR MYCORRHIZA ON ACETYL-CoA CARBOXYLASE ACTIVITY AND OIL CONTENT OF Jatropha curcas L. - Puspitaningsih, Yanni
Seedlings of Jatropha curcas can be obtained from cuttings. However, root system of cuttings less developed compare to that of seed embryo. Thus, in order to improve the absorption of nutrients, Vesicular Arbuscular Mycorrhiza (VAM) has been added into the plant. The presence of VAM is suggested could increase plant growth and seed production with respect to the content of oil. The application of VAM to J. curcas had been performed by previous researchers, Kerana and Puspanikan (2008) to harvest the first yields. This research was the continued examination in order to observed the second yields. The objective of this research was to increase the oil yield and to investigate the correlation of ACCase enzyme activity with the oil-yield. J. curcas had been planted planted on the soil with the addition of VAM as much as 500 spores/plant (B1), 1000 spores/plant (B2), 1500 spores/plant (B3), and with no addition of VAM as a control (B0). The effect of VAM on J. curcas was observed on the degree of root infection, the amount of fruit for each plant, the fruit diameter, the seed weight, the ACCase enzyme activity, and the seed oil content. The degree of root infection was observed on week 60, 64, and 68, the amount of fruit for each plant was observed on week 60 after the treatment, the mature fruit diameter was measured using vernier calipers, the seed weight was weighted by using analytical scale, ACCase activity was analyzed by measuring the formation of malonyl-CoA concentration by HPLC (High Performance Liquid Chromatography). In order to obtain the oil : the seed was extracted with hexane using Soxhlet aparatur. The hexane extract was collected and evaporated in rotary evaporator to obtain the oil. Those data were analyzed using ANOVA and further analyzed with Post Hoc-Duncan. The results showed that the addition of VAM into J. curcas caused root infection with the degrees of infections in B1 plant were 33.33%, 48.33%, and 50.00%; in B2 plant were 36.67%, 51.67%, and 51.67%; in B3 plant were 70.00%, 73.33%, and 73.33% respectively on the week 60, 64, and 68. An infection was also detected in plant without VAM (B0) with the degree of infection were 23.33%, 35.00%, and 36.67%, on the week 60, 64 and 68, respectively. The amount of fruit for each plant and the diameter of fruit were not significantly different among the tested plant (B0, B1, B2 and B3). On the other hand, the seed weight on the B3 plant was significantly higher that of weight at others tested plants, i.e., 770 mg in B3 plant, 760 mg in B2 and B1 plant, and 740 mg in B0 plant. The activity of ACCase in control plant (B0) was increased from 6th to 10th week after fruiting (from 16.81 x 10-4 unit to 23.32 x 10-4 unit). ACCase activity in B1 and B2 plants increased from 4th to 10th week after fruiting, B1 plant from 7.38 x 10-4 unit to 29.67 x 10-4 unit and B2 plant from 10.49 x 10-4 unit to 30.84 x 10-4 unit. ACCase activity in B3 plant increased from 2nd to 10th week after fruiting (from 1.93 x 10-4 unit to 32.53 x 10-4 unit). The seed oil content was positively correlated to the amount of added VAM spore. Based on the dry weight of seed, the percentage of oil was 46.42%, 47.50%, 48.48%, and 51.30% in seed plants of B0, B1, B2, and B3, respectively. In conclusions that the addition of VAM into root of J. curcas in the range of 500 – 1500 spore/plant significantly increase the weight of seed, the activity of ACCase and the oil content with the highest weight is 770 mg, the highest activity of ACCase is 32.53 x 10-4 unit and the highest oil content is 51.30%.